An Acoustic Approach to Backed /r/ Realizations in Puerto Rican Spanish - Alba Arias Alvarez (Languages)
Trill realizations present a wide range of cross-dialectal variation in Spanish, especially in Puerto Rican Spanish (PRS). The backed /r/ in, e.g., [ká.xo] for carro, is not an exception. Since analysis with continuous variables has advanced the research on fricative variation among other Spanish varieties, the present study considers center of gravity values to provide an acoustic analysis of the backed /r/ realizations in Puerto Rican Spanish, both on the island of Puerto Rico and within the Puerto Rican diasporic community in Holyoke, Massachusetts (United States). The following three experimental production tasks were designed and employed: a picture description task, a map task, and a reading task. Furthermore, 45 participants performed the experimental tasks, i.e., 21 were recorded on the island and 24 in Holyoke. Findings show that the distribution of center of gravity values falls on a continuum, which can be affected by linguistic and sociolinguistic variables, in line with previous research on fricatives.